Dragon Quest monsters+. 2 - Yoshizaki, Mine; Lumsdon, David (Comic book writer) (Seven Seas Entertainment, 2019)
Kleo, now a Monster Master, survives an attack by the Dragonlord and sets out on a dangerous mission to rescue Terry, the kingdom's last champion, with only a slime and a junior dragon helping him.